'Horrent with Mysterious Spiculæ'. Augustus De Morgan's Logic Notation of 1850 as a 'Calculus of Opposite Relations'. Issue 1 (2nd January 2018) - Heinemann, Anna-Sophie
Abstract : The present paper expounds the logic notation proposed by Augustus De Morgan in 1850 from within the original context of De Morgan's account of syllogistic logic and his approach to quantification. The notational system of 1850 is shown to be a flexible tool to state inferences, to prove their validity and to derive formulæ of the respective system by 'blind' application of transformation rules. These pertain to the swapping of operator signs, which are of inverse 'character' in a two-fold sense: The signs both represent inverse operations and exemplify oppositeness due to their very shapes. Thus, while De Morgan's initial choice of symbol shapes is due to certain diagrammatic features, his notational system of 1850 leads to an account of logical operations as effected by manipulation of symbol tokens. It is concluded that as an instantiation of what De Morgan terms a 'calculus of opposite relations', his notation of 1850 may also be conceived of as a 'graphicism' affording for the working of a 'symbolic machine' on (intermediate) 'de-semantification'.